Starlink for Papua: Policy Analysis to Bridge the Digital Gap in Improving the Quality of Education - Vicy Reynaldo Parlindungan Manurung; Mufarrihul Hazin; Mohammad Syahidul Haq; Amrozi Khamidi; Muhammad Sholeh; Andi Kristanto (International Journal of Emerging Research and Review, 2026)
Objective: This study analyzes the implementation of the Starlink satellite internet policy in remote educational settings as a strategic intervention to bridge the digital divide and improve education quality, focusing on Satap Tawar School in Kampung Tawar, Fakfak Regency, West Papua. Method: This qualitative case study collected primary data through semi-structured interviews with school principals, teachers, students, and education policymakers, complemented by participatory observation and documentation studies. Thematic analysis was guided by an integrated framework of digital divide theory, policy implementation theory, and technology acceptance models. Data validity was ensured through triangulation of sources, methods, and member checks. Results: Starlink access has significantly transformed educational practices across three dimensions: (1) digital learning accessibility, enabling teachers to access e-books and video tutorials while students gain diverse digital references; (2) teaching quality, with educators integrating visual media and interactive content beyond conventional resources; and (3) student participation, marked by improved motivation and attendance. However, critical constraints persist: limited teacher digital literacy, inadequate hardware availability, operational cost burdens, and insufficient local technical support. These findings confirm that Starlink's success depends not merely on technical infrastructure but crucially on institutional capacity, pedagogical readiness, and sustained government support. Novelty: This study provides the first empirical evaluation of Starlink policy in Indonesia's education sector within extreme geographic conditions. It offers a comprehensive analysis integrating policy implementation, institutional readiness, and socio-technical dynamics, demonstrating that first-level digital access does not automatically translate into educational benefits without adequate capacity-building. These findings provide valuable lessons for developing countries facing similar digital divide challenges.